Curability difference between autochthonous mouse tumors and their transplants in association with immune gene expression - Hiroshi Tanooka; Chie Kudo-Saito; Fumiko Chiwaki; Masamichi Ishiai; Kouichi Tatsumi; Hiroki Sasaki; Takahiro Ochiya (PLoS ONE, 2026)
Compared with transplanted tumors, autochthonous tumors are difficult to cure using experimental radiation therapy in mice. Here we analyzed differences in immune-related gene expression profiles between mouse fibrosarcomas subcutaneously induced by 3-methylcholanthrene (3MC) and their corresponding transplanted tumors. The immune genes examined were Pd1 , Pdl1 , Pdl2 , Cd3d , Cd8a , Cd8b , Ifnγ , Itga2 , Gzmb, and Foxp3 . Among 12 tumors, one was non-transplantable and showed a benign phenotype with an abundance of DX5 + natural killer cells and CD8 + T cells together with increased IFNγ expression and mRNA levels of all immune genes except for Itga2 . The other 11 transplantable tumors showed increased expression of Pd1 , Pdl1 , Pdl2 , Cd3d , Cd8b , and Ifnγ following transplantation into syngeneic mice. These effects of transplantation highlight the relevance of immune gene expression status to the curability of tumors.